The Woman (In) Question: Gender, Politics, and Edward Bulwer-Lytton's Lucretia. - Ciolkowski, Laura (Novel: A Forum on Fiction)
Explores the `forgery' of femininity in Edward Bulwer-Lytton's `Lucretia: or, the Children of Night' (1846), which explicitly inserts itself into the debates about `The Woman (in) Question.' Bulwer's forgery of female subjectivity in `Lucretia'; Ideal self; The forgery of femininity by the figure of Lucretia; More.